Construction and Validation of the System of Medicine Choice Scale in the Indian Context - Sorabh Lakhanpal, Dr. Pavitar Parkash Singh, Rajib Chakraborty (International Journal of Advanced Science and Technology, 2020)
The researchers tried to develop a scale to measure the choice of system of medicine by patient in the Indian context. 471 acute and chronic diseases patients who sought treatment for their ailment in the last one year from various cities of the Indian state of Punjab, were the sample subjects of this study. Exploratory factor analysis was conducted using SPSS Statistics Ver.23.0 to extract factors. The determinant was well above 0.00001 at 0.003. The KMO was excellent at 0.947. The Bartlett’s test of sphericity was also significant. The Principal Component Analysis method of extraction with direct oblimin technique produced three factors with strong eigen values of 5.013, 4.662 and 4.444, and explained 43.333 % total variance, when 5 out of the 26 items from the pool were eliminated. The three factors had eight, seven and six items in them with the Cronbach’s alpha measure of reliability 0.796, 0.768 and 0.751 respectively. The sub-scales displayed similar Raykov’s composite reliability estimate too. SPSS AMOS Ver. 23.0 was used to conduct confirmatory factor analysis. All the goodness of fit indices including CMIN/DF and RMSEA were found to be satisfying their benchmark values, except RMR. The scale is found to display good psychometric properties and requires further validation in other culturally diverse contexts in India. Implications of the study are discussed.